Combined Free Flap Reconstruction Following Head And Neck Cancer Resection: Chimeric And Double Free Flap Reconstruction - Atmodiwirjo, Parintosa; Anggrahita, Tasya (Lingkar Studi Bedah Plastik Foundation, 2018)
Background: Head and neck reconstruction following cancer resection remains a challenge for surgeons. Microsurgical free tissue transfer is the technique of choice to close the defect. Extensive complex defects resulted from radical excision often require two free flaps to provide adequate bony structure and soft tissue coverage. Method: Three cases following head and neck cancer resection that require reconstruction with two combined free flaps were reported. The combination of two free flaps between vastus lateral free flap, radial forearm free flap, and free fibular flap was reviewed in this study. The patients were then followed up for 1-2 months. Result: Two of the patients had a flow through chimeric free flap between radial forearm free flap and free fibular flap to reconstruct the maxillary, palatal and mandibular defect. One patient had a combination of free fibular flap and vastus lateral free flap to reconstruct the mandibular defect. No complications were observed in all patients. All the flaps were vital without donor site morbidity. However, two patients needed secondary procedures for further reconstructions. Conclusion: Combined free flaps are reliable for closing the complex defect after wide resection of head and neck cancer. They can provide adequate tissues, reduce recipient site morbidity, permit simultaneous reconstruction with two-team approach. Therefore, provide a practical method of defect coverage for these patients.